Interconnection between actin cytoskeleton and plant defense signaling - Janda, Martin; Matoušková, Jindřiška; Burketová, Lenka; Valentová, Olga (Plant signaling & behavior, 2014)
Actin cytoskeleton is the fundamental structural component of eukaryotic cells. It has a role in numerous elementary cellular processes such as reproduction, development and also in response to abiotic and biotic stimuli. Remarkably, the role of actin cytoskeleton in plant response to pathogens is getting to be under magnifying glass. Based on microscopic studies, most of the data showed, that actin plays an important role in formation of physiological barrier in the site of infection. Actin dynamics is involved in the transport of antimicrobial compounds and cell wall fortifying components (e.g. callose) to the site of infection. Also the role in PTI (pathogen triggered immunity) and ETI (effector triggered immunity) was recently indicated. On the other hand much less is known about the transcriptome reprogramming upon changes in actin dynamics. Our recently published results showed that drugs inhibiting actin polymerization (latrunculin B, cytochalasin E) cause the induction of genes which are involved in salicylic acid (SA) signaling pathway. In this addendum we would like to highlight in more details current state of knowledge concerning the involvement of actin dynamics in plant defense signaling.
Keywords: transkriptom; rostliny; imunita rostlin; Signal Transduction; Plant Immunity; Actin Cytoskeleton; Actins; signální transdukce; Transcriptome; aktiny; Plants; mikrofilamenta